2022
DOI: 10.3389/fpsyg.2022.934423
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Behavioral Intention and Use of Interactive Whiteboard by K-12 Teachers in Remote and Rural Areas

Abstract: Interactive Whiteboard (IWB) has recently been used to replace the TWB (traditional whiteboard), with many of its features being observed to help teachers in educational activities. This is based on effectively and efficiently increasing the teacher-student interaction. Therefore, this study aims to analyze the determinants of Behavioral Intention (BI) and the use of interactive whiteboards by K-12 teachers, in remote and rural Chinese areas. The Modified-Unified Theory of Acceptance and Use of Technology 2 (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 105 publications
4
26
1
Order By: Relevance
“…-In order to use interactive technology effectively, especially to cover and thoroughly study the required material, the educator must plan the work carefully. This will allow to set preparatory tasks for the students, to select interactive exercises for the lesson that would give them the 'key' to learn the material, conditions in which students would be forced to take it seriously rather than performing it mechanically or "playfully" (Zhou, Li, & Wijaya, 2022);…”
Section: Resultsmentioning
confidence: 99%
“…-In order to use interactive technology effectively, especially to cover and thoroughly study the required material, the educator must plan the work carefully. This will allow to set preparatory tasks for the students, to select interactive exercises for the lesson that would give them the 'key' to learn the material, conditions in which students would be forced to take it seriously rather than performing it mechanically or "playfully" (Zhou, Li, & Wijaya, 2022);…”
Section: Resultsmentioning
confidence: 99%
“…The data were analyzed using SPSS 22 and smart PLS 3.0 software, which is suitable for testing hypotheses and helping new research models. Furthermore, The partial least square method structural equation model (PLS-SEM), which is a nonparametric approach, can be used to test many variables and path relationships simultaneously [ 60 , 61 ]. More specifically, it is used to visualize and explain the variance that exists in endogenous variables.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, it is used to visualize and explain the variance that exists in endogenous variables. This software is widely used to test theories that are predicted from the results of a literature review [ 61 ]. Several studies consider the PLS-SEM technique more flexible and accurate for quantifying measurement models [ 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is an important factor used to predict an individual's intention and acceptance to use technology in both the UTAUT and BI models (Wijaya et al, 2022b). Social influence in previous studies has also been shown to affect EE (Shiferaw et al, 2021;Zhou et al, 2022). Support from the environment to use new technology drives an individual to feel that the technology is not difficult.…”
Section: Social Influencementioning
confidence: 99%